2019
DOI: 10.3390/info10100303
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable and Open Access Knowledge Organization Model to Preserve Cultural Heritage and Language Diversity

Abstract: This paper proposes a new collaborative and inclusive model for Knowledge Organization Systems (KOS) for sustaining cultural heritage and language diversity. It is based on contributions of end-users as well as scientific and scholarly communities from across borders, languages, nations, continents, and disciplines. It consists in collecting knowledge about all worldwide translations of one original work and sharing that data through a digital and interactive global knowledge map. Collected translations are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Over 30 translations were obtained, and on the base of their content, 10 parallel corpora were built. The authors reported further that during the process, 22 under-represented languages were identified amongst all gathered full-text translations [60], which is a sign of the impressive scale of response from end-users, and of a promising potential for the future of this project.…”
Section: Culturementioning
confidence: 85%
See 2 more Smart Citations
“…Over 30 translations were obtained, and on the base of their content, 10 parallel corpora were built. The authors reported further that during the process, 22 under-represented languages were identified amongst all gathered full-text translations [60], which is a sign of the impressive scale of response from end-users, and of a promising potential for the future of this project.…”
Section: Culturementioning
confidence: 85%
“…Fraisse et al [60] express their conviction that language is one of the most important barriers that pose an obstacle to the sustaining of global knowledge diversity. The authors indicate that a number of efforts that have been taken by the LIS community, e.g., KOS' development, making progress in the IRs discipline, outworking of metadata exchanging standards, and multilingual electronic libraries and archival projects, all help to create efficient, cheap, and reliable resources for the purpose of preserving rare or expiring languages [60]. Apart from that, they claim that the language barrier is also a central issue, which has to be addressed by International Society for Knowledge Organization (ISKO) authorities.…”
Section: Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In a case study of comparing human and machine translations, Ahrenberg (2017) suggested that the human translator used several procedures that seem to be beyond the reach of the MT system (such as sentence splitting, shifts of phrase function and/or category, explicitation, modulation and paraphrasing). The project of Fraisse et al (2019) aims to preserve cultural heritage and language diversity by analyzing the translation adaptations in multilingual corpora of translated literary texts, which is particularly important for low-resource languages. In order to provide insights for discourse-aware MT system's development, discourse-related language contrasts are analyzed for English-Croatian and English-German (Lapshinova-Koltunski and Hardmeier, 2017;Šoštarić et al, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…Some studies use crowdsourcing approaches to annotate lexicons [20] and collect speech recognition data [21] for low-resource languages. Some other research proposes a collaborative model for different types of volunteers and contributors to take part in the knowledge organization process for sustainable preservation of language diversity and succeeds in building multilingual parallel corpora for low-resource languages [22,23]. However, it is always time consuming and costly to create resources and NLP tools for low-resource languages when starting from scratch.…”
Section: Introductionmentioning
confidence: 99%